A The Acute Effects of Sport Massage on Decreased Heart Rate After Exercise (Case Study on PSHT Pencak Silat Athletes in Karangsambung) - Hasanah, Sofiatun; Sumartiningsih, Sri; Muhibi, Muhamad (Journal of Physical Education and Sports, 2023)
Physical activity directly affects the cardiovascular system, both acute and chronic effects. The acute effect of physical exertion is an increase in heart rate. This increase needs to be lowered so that the body returns to its original condition. The purpose of this study was to determine the effect of acute sport massage on the speed of pulse rate reduction after exercise. Method used in this study is quasi-experimental. Quasi experiment with one grou pre-test and post-test research design, the sample is a popda pencak silat athlete psht karangsambung district. The data collection technique used a side kick test for 1 minute as many as 40 kicks, and was calculated using a digital tension meter and stopwatch. Then massage will be given for 20 minutes on the gastrocnemius repetisis muscle movement 3-5 times. Data were analyzed using paired sample t-test the pre-test and post-test mean values were 20.167, the standard deviation values were 9.094, t tables were 7.682, degrees of freedom were 11, and p values were 0.000. The results of the research data show a p value of 0.000, then the p <0,05, therefor H0 is rejected and Ha accepted. The results of this study showed that sports massage given for 20 minutes to the gastrocnemius muscle after physical activity affected the rate of lowering heart rate in athletes.